Developing structure and thermodynamic properties-consistent coarse-grained model for random copolymer systems. (11th August 2017) - Li, Bei; Chen, Qiubo; Huang, Shangyu; Liu, Hanxing
Abstract: Molecular characterizing of random copolymer systems at large timescales is significantly important in prediction and advancing understanding of materials properties and phenomena. In this paper, we present a hybrid structure and thermodynamic properties-consistent method to develop a quantitative coarse-grained (CG) model for perfluoropolyethers (PFPEs). The bonded potentials were derived via iterative Boltzmann inversion by reproducing the distributions of bond distances and angles from the reference atomistic simulations. A novel analytical form based on multi-centered Gaussians was then introduced for the first time to represent the resultant tabulated bonded potentials well. Moreover, the non-bonded potentials were denoted by the Lennard-Jones potentials and the parameters were devised by directly matching the temperature–dependent density and surface tension of the CG models and the experiments. The transferability of the CG potentials to target PFPEs with higher molecular weights was also validated. The hybrid method in this work is of particular value and provides a guideline in developing analytical and quantitative CG potentials for random copolymers rationally. Graphical abstract: Highlights: A hybrid coarse graining method for random copolymers was proposed. Multi-centered Gaussians were introduced to express bond and angle potentials. The molecular-fragment transferability of the coarse-grained model was illustrated.